2012
DOI: 10.18388/abp.2012_2127
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for RNA isolation from plants using commercial extraction kits.

Abstract: Isolation of RNA from plants rich in secondary metabolites using commercial kits often results in contaminated preparations which are not suitable for downstream applications. Although many specific protocols appropriate for plants with a high content of phenolics, anthocyanins and polysaccharides have been developed, these are often expensive, time consuming and not applicable to different types of tissues. This study presents a simple and efficient modification of RNA extraction from different types of tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…RNA was extracted from approximately 50 mg of homogenised oak tissue using a modified procedure for isolating RNA from woody plant material [ 31 ]. Briefly, 5 ml of extraction buffer (4 M guanidine thiocyanate, 0.2 M sodium acetate pH 5.0, 25 mM EDTA, 2.5% ( w / v ) polyvinylpyrrolidone and 1% ( v / v ) β-mercaptoethanol) was added to oak tissue kept frozen in a sterilised mortar using liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from approximately 50 mg of homogenised oak tissue using a modified procedure for isolating RNA from woody plant material [ 31 ]. Briefly, 5 ml of extraction buffer (4 M guanidine thiocyanate, 0.2 M sodium acetate pH 5.0, 25 mM EDTA, 2.5% ( w / v ) polyvinylpyrrolidone and 1% ( v / v ) β-mercaptoethanol) was added to oak tissue kept frozen in a sterilised mortar using liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…To test this, we have tried to homogenize young grape leaves in lysis buffer with mortar and pestle without liquid nitrogen (Method C) and it produced 67 % higher yield of total RNA than that of the method A (data not shown). Kalinowska et al [ 48 ] also reported that further grinding plant tissues in extraction buffer after the initial grinding in liquid nitrogen greatly increased the RNA yield.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA extractions from N. benthamiana and blackcurrant were carried out using QIAGEN’s RNeasy Plant Mini Kit (cat. # 74904, QIAGEN, Toronto, ON, Canada) using the modified protocol described by Kalinowska et al [ 33 ]. Total RNA was eluted in 50 µL diethylpyrocarbonate-treated H 2 O.…”
Section: Methodsmentioning
confidence: 99%